What Triggers transient AIDS in the Acute Phase of HIV Infection and chronic AIDS at the End of the Incubation Period?. Issue 2 (2007) - Kramer, Ivan
Abstract : Novel dynamical models are introduced demonstrating that the T helper cell (THC) density drops in the acute infection phase of HIV infection, sometimes causing transient AIDS, and at the end of the incubation period causing chronic AIDS have a common dynamical cause. The immune system's inability to produce enough uninfected THCs to replace the infected ones it is destroying causes a drop in the THC density at any stage of HIV infection . Increases in viral infectivity, probably caused by random mutation of HIV, are shown to drive the progression of the infection. The minimum incubation period for the long term non-progressors (LTNPs) was calculated from a novel physical model: 0.3% of infecteds have incubation periods of 23.1 years or more, and there is no biomedical difference between LTNPs and progressors. Chronic AIDS is shown to result from three random transitions linking four clinically-distinct stages of HIV infection following seroconversion.